The Effect of Polyacrylamide Polymer Stabilization Soil on the Magnitude of Settlement and Stability of Bridge Approach Slabs - Mulyadi Yuswandono; Dewi Amalia; Rahmat Permana; Hendry; Muhammad Bayu Arofah; Raihan Maulana Sulaiman; Suliman Badawi Ahmed (Department of Civil Engineering, Politeknik Negeri Bandung, 2024)
The main problems that often occur in embankments built on soft soil are subsidence of the subgrade and stability of the embankment. This research aims to determine the effect of applying silty clay soil stabilized by PAM on subgrade subsidence and embankment operation stability. Apart from that, this research also analyzes the effect of variations in slope on subgrade subsidence and embankment stability. Analysis uses the finite element method with Plaxis 2D V20 software. From the analysis results it is known that the use of 0.2% PAM stabilized silty clay backfill material; 0.4%; 0.6%; 0.8%; and 1% has a higher Safety Factor (SF) value than the selected embankment, where the SF increase is 28.72%; 29.90%; 30.81%; 32.75%; and 33.10%, respectively. The use of silty clay material stabilized by PAM (0.2%; 0.4%; 0.6%; 0.8%; and 1%) succeeded in reducing settlement occurring in the field respectively by 10.23%; 6.77%; 5.79%; 4.41%; and 1.09%. This means saving on the need for stockpiled materials. Variations in slope affect the decrease in the stability of the subgrade and embankments, where the smaller the slope angle, the smaller the subsidence of the subgrade and the greater the value of the embankment stability safety figure obtained.